Uma análise das metafunções da gramática do design visual em videoanimação: possibilidades para a leitura de textos em movimento - Silva, João Miller da (2021)
Recurrently, research on images, both static and in motion, has assumed a prominent position in linguistic science, since they bring together different multisemiotic resources that are deci-sive for the process of producing meanings. With the expansion of the circulation of texts with diverse semiotic resources, through the democratization of Internet access, new reading skills are demanded of the subject-to-reader in social interactions. In view of the above, the Grammar of Visual Design, (KRESS; VAN LEEUWEN, 2006 [1996]) presents itself as a theoretical pro-posal aimed at the analysis of semiotic resources in the textualization of static multisemiotic texts. Intending to extend the contributions of this theory, the present work proposes to reflect on the possibilities of GDV for the study of texts in motion, more specifically for the analysis of the textualization processes of video animations. In this sense, the present work aims to pre-sent, through the analysis of video animation Snack attack (2012), the contributions of different languages to the meaning production, based on the representational, interactional and compo-sitional metafunctions of the Grammar of Visual Design. The study is based on theories of the video animation genre (FERREIRA; CARDOSO; FURTADO, 2019); in Social Semiotics (LIMA, 2015); and in the Grammar of Visual Design (KRESS; VAN LEEUWEN, 2006). As a result of this research, some points deserve to be highlighted: (a) studies on the video-animation genre are scarce, even though it is a very recurrent genre in social daily life; (b) the analysis of video animations can represent a notably substantial strategy for the formation of critical read-ers, due to the different issues that can be elected for discussion; (c) the discussion on studies involving the Theory of Multimodality, Social Semiotics and GDV can favor the understanding of the various languages that make up the textualization process of multisemiotic texts; (d) the representational meta-function can contribute to an analysis of the choices related to the con-struction of the characters, the problematization of ideological positions and the articulation with the context of production, circulation and reception of texts .; (e) the interactional meta-function can favor the understanding of the strategies used by the producers for the establish-ment of the interactions between the interlocutors, either to arouse the reader’s interest, or to reinforce the strength of the argumentative and persuasive speeches; (f) the compositional meta-function can provide the observation of details of the textualization process and the understand-ing of the resources that were highlighted in the project’s construction of saying and that pro-vide clues to the interpretative path; (g) the understanding that, while safeguarding specificities, GDV brings substantial contributions to the analysis of texts in motion, enabling the systema-tization of issues to illuminate a more in-depth and critical reading of the different choices made by producers. It is believed that the research carried out may have contributed to the provocation of new studies about the contributions of GDV to the study of multisemiotic texts in motion, since the video-animation’s analysis signaled that the reading process may be more can be more productive and more fruitful if the mechanisms of textualization are analyzed from different perspectives.